Board diversity and firm performance: an empirical investigation in the Brazilian market - João Batista Fraga (FUCAPE Business School, 2012)
This article investigates the diversity of the boards of directors of Brazilian companies listed on the BM&FBovespa with respect to gender, age, educational attainment and independence, to ascertain whether there is a relationship between any of these diversity measures and firm performance. The study covers all companies without majority control, a type of corporate structure that first appeared in Brazil in 2005. The results indicate that greater diversity in the educational disciplines and the presence or absence of independent board members negatively affect performance, while diversity in years of schooling has a positive effect. The presence of women board members is small, but firms that have at least one female director outperform those that do not.